Causing Global Warming - Gunnemyr, Mattias (Ethical theory and moral practice, 2019)
Do I cause global warming, climate change and their related harms when I go for a leisure drive with my gas-guzzling car? The current verdict seems to be that I do not; the emissions produced by my drive are much too insignificant to make a difference for the occurrence of global warming and its related harms. I argue that our verdict on this issue depends on what we mean by 'causation'. If we for instance assume a simple counterfactual analysis of causation according to which 'C causes E' means 'if C had not occurred, E would not have occurred', we must conclude that a single drive does not cause global warming. However, this analysis of causation is well-known for giving counterintuitive results in some important cases. If we instead adopt Lewis's (2000) analysis of causation, it turns out that it is indeterminate whether I cause global warming (etc.) when I go for a single drive. Still, in contexts where we seek to control or understand global warming, there is a pressure to adopt a more fragile view of this event. When we adopt such a view, it turns out that a single drive does cause global warming (etc.). This means that we cannot like Sinnott-Armstrong (2005) and Kingston and Sinnott-Armstrong (2018) reject the idea that I should refrain from going for a leisure drive simply because such a drive does not cause global warming.